2020
DOI: 10.2147/ott.s273108
|View full text |Cite
|
Sign up to set email alerts
|

<p>Synergistic Effect of 3-Bromopyruvate in Combination with Rapamycin Impacted Neuroblastoma Metabolism by Inhibiting Autophagy</p>

Abstract: Background Alterations in the cell metabolism, such as enhanced aerobic glycolysis, have been identified as a prominent hallmark of cancer cells. 3-Bromopyruvate (3-BrPA) is a proverbial hexokinase (HK)-II inhibitor, which can inhibit cancer cell energy metabolism. Rapamycin is a new type macrocyclic lactone, which can inhibit the serine/threonine protein kinase mTOR. In order to comprehend the influence of 3-BrPA on autophagy activity in vitro, we conducted a series of experiments using different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Interestingly, 3BP decreased proliferation and colony formation, in addition to triggering cell death regardless of PLX presence, indicating that 3BP presents cytostatic and cytotoxic effects on melanoma cells. These results agree with the literature, which shows that 3BP can both arrest the cell cycle [ 50 , 51 , 52 ] and trigger apoptosis/necrosis [ 53 , 54 ] in various types of tumors. However, as concentrations of 3BP greater than 60 μM can completely deplete cellular ATP [ 55 ], we hypothesized that necrosis might be the principal mechanism of 3BP in the SKMEL28R cell line.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, 3BP decreased proliferation and colony formation, in addition to triggering cell death regardless of PLX presence, indicating that 3BP presents cytostatic and cytotoxic effects on melanoma cells. These results agree with the literature, which shows that 3BP can both arrest the cell cycle [ 50 , 51 , 52 ] and trigger apoptosis/necrosis [ 53 , 54 ] in various types of tumors. However, as concentrations of 3BP greater than 60 μM can completely deplete cellular ATP [ 55 ], we hypothesized that necrosis might be the principal mechanism of 3BP in the SKMEL28R cell line.…”
Section: Discussionsupporting
confidence: 92%
“…Gan et al . reported that 3-bromopyruvate (3-BrPA), a hexokinase (HK)-II inhibitor, combined with rapamycin, synergistically suppressed aerobic glycolysis in NB cells [ 41 ]. Song et al .…”
Section: Discussionmentioning
confidence: 99%
“…Further pre-clinical studies also showed that 3-BP enhance apoptotic cell death in doxorubicin-resistant NB cell lines (Bean et al, 2014), and combination treatment of 3-BP + rapamycin synergistically induced apoptosis, cell cycle arrest and inhibition of cytoprotective autophagy (which will be discussed in Section 5.0) in NB cells (Gan et al, 2020). The second generation of 3-BP, known as 177 Lu-3BP-227 in Phase I clinical trial (NCT03525392) for adult solid tumour expressing neurotensin receptor type 1 (NTR1) and showed an anti-tumour effect in metastatic pancreatic adenocarcinoma (Baum et al, 2018).…”
Section: Targeting Bioenergetics Pathways To Induce Apoptosismentioning
confidence: 93%
“…Pre-clinical NB (Bean et al, 2014;Gan et al, 2020;Matsushita et al, 2012) Phase I Adult solid tumours…”
Section: -Dg Glycolysis Inhibitormentioning
confidence: 99%